Defesa antioxidativa em plantas de arroz duplamente silenciadas nas APXs citosólicas e expostas a estresses abióticos. - Fontenele, Adilton de Vasconcelos (2011)
The aim of this study was to characterize physiological and biochemical aspects that show if rice plants (Oryza sativa) knockdown on cytosolic ascorbate peroxidase enzyme (cAPX) are more susceptible to oxidative stress than the wild type plants. APX is an important enzyme from oxidative metabolism of plants, acting on regulation of the endogenous levels of hydrogen peroxide (H2O2). For this, rice plants knockdown on cAPX (Apx1/2s) and wild type (WT) were used for the experimentation. The plants were silenced by interference RNA technical (iRNA) and were grown for 35 days into 1.5 L pots containing nutritive solution under greenhouse conditions. The experiment I was performed with leaves segments immersed in methyl viologen (MV) 50 μM for 24h and the experiment II was performed by application of the following treatments: salt stress, high light and MV. The results from experiment I shown Apx1/2s plants have a higher level of H2O2 high than the levels found on WT rice plants, suggesting that Apx1/2s plants present a level of H2O2 near a level of cell signaling. The fact of WT plants had accumulated H2O2 1h after the treatment suggest the necessity of a signaling H2O2 level for stimulate defense systems. Apx1/2s plants unlike of WT plants presented a constant decline on H2O2 content, indicating a likely H2O2 scavenging excess. After 3h of treatment the chloroplastic enzymes SOD, APX and PHGPx presented upper active in Apx1/2s plants, in control and stress, compared with WT plants. These results suggest the existence of an antioxidant system quite active in the Apx1/2s plants. In experiment II the Apx1/2s plants presented no differences in the photochemical parameters when compared with WT plants, even possessing a smaller photosynthesis under controlled conditions. The energy dissipation (NPQ) in the Apx1/2s plants under high light was, in average, higher than WT plants, suggesting better energy dissipation. Even with efficient energy dissipation, the plants could not avoid the excess of energy in the photosystem and they suffered photoinhibition and damage in photosynthetic apparatus (Fv/Fm). In relation the WT plants, Apx1/2s plants presented a higher activity of antioxidant enzymes SOD, CAT and PHGPx under controlled conditions, probably intending compensate the lack of cAPX. In the MV treatment the chloroplastic PHGPx was stimulated above 100% in the Apx1/2s plants, indicating that these plants can repair oxidative damage faster than the WT plants. The results suggest that Apx1/2s plants, despite the absence of cAPX, activated additional security systems to compensate the lack of cAPX and respond quickly and efficiently to stress situations.